Newsprint Grade Groundwood Pulp from Abies pindrow Royle (Silver Fir) - Bhat, R. V.; Guha, S. R. D.; Virmani, K. C. (Indian Forester, 1960)
Laboratory experiments on the production of mechanical pulps from Abies pindrow (Silver fir) are described. Standard pulp sheets were made from 100 per cent mechanical pulp from this species and from a mixture of 70 per cent mechanical pulp and 30 per cent bleached bamboo chemical pulp. Strength properties of the standard sheets prepared from the mechanical pulp produced under suitable conditions have shown that this wood is a suitable raw material for the production of newsprint.